UTILIZING REAP STRATEGY (READ-ENCODE-ANNOTATE-PONDER) TO ENHANCE LEARNERS' READING COMPREHENSION ACROSS VARIED READING HABITS - Kiki Rizki Amelia; Eva Saptarina; Rachmanita Rachmanita; Ratna Nery; Fitri Novia; Dewi Sartika; Rekha Asmara (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2024)
This study investigates the impact of the REAP (Read, Encode, Annotate, Ponder) strategy on students’ reading comprehension across different reading habits. The research was conducted with 10 second-semester students from the English Language Education program at FKIP UNISKI Kayuagung. This study applied a quantitative method with a pre-experimental design. A reading habits questionnaire and a reading comprehension test were employed to collect the data. The data were analyzed using descriptive statistics and t-tests. Results indicated significant improvements in reading comprehension following the implementation of the REAP strategy, with high and low reading habits groups showing substantial gains. The REAP guided students to listen and read in the reading phase, and then encoding helped them to rephrase their ideas. After that, they could highlight the key points in annotation. Finally, they did group discussions. This process boosts comprehension for all students, regardless of reading habits. Additionally, student perceptions of the REAP strategy varied, with those possessing strong reading habits responding more positively. These findings suggest that the REAP strategy is an effective tool for enhancing reading comprehension across reading habits, fostering skill refinement in proficient readers and marked improvement in less proficient ones.